2013
DOI: 10.1007/s13224-013-0473-4
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Review Sex Ratio at Birth and Analyze Preferences for the Sex of the Unborn

Abstract: Objectives (1) To study the status of sex ratio at birth with increasing birth order, (2) To ascertain the relationship of declining sex ratio with respect to socio demographic factors. (3) To study outlook of patient towards sex preference, willingness to determine sex of the fetus, wish to terminate the pregnancy in case of unwanted sex of the baby. Methods This is the retrospective study done in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
3
3
0
Order By: Relevance
“…20 In addition, the authors found that the participants' gender preference for their current pregnancy was shaped by the gender of the children they already had. 21 In other words, their findings were in agreement with those in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…20 In addition, the authors found that the participants' gender preference for their current pregnancy was shaped by the gender of the children they already had. 21 In other words, their findings were in agreement with those in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Another study reported that 40% of primiparous women had a gender preference during their pregnancy for their babies, while this figure was 88% for multiparous women . In addition, the authors found that the participants' gender preference for their current pregnancy was shaped by the gender of the children they already had . In other words, their findings were in agreement with those in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Another study conducted in India showed that the sex ratio was 972 females per 1,000 males in primipara, which decreased to 879 females per 1,000 males in second para and further reduced to 784 females per 1,000 males in third para. With increase in parity, there was decline in number of females per 1,000 males 15 which was also the case in this study.…”
Section: Discussionsupporting
confidence: 82%
“…[ 3 ] Sex ratio at birth is considered to be more accurate indicator of sex selection as it indicates the factors that come into play before birth. [ 4 ] India's sex ratio at birth was 919 females per 1000 males while in rural area sex ratio was 927 and even lower in the urban area i.e., 899. [ 3 ] After relentless efforts of activists, a law was passed in Maharashtra known as Maharashtra Regulation of Pre-Natal Diagnostic Techniques (PNDT) Act, 1988.…”
Section: Introductionmentioning
confidence: 99%